THE EFFECT OF PRODUCT QUALITY, PRICE PERCEPTION AND PROMOTION ON REPURCHASE INTEREST (EMPIRICAL STUDY ON CONSUMERS OF SCARLETT SKINCARE USERS IN SEMARANG CITY) - Jihan Salsabella Ayu Andini; Euis Soliha (SEAN Institute, 2023)
This study examines the effect of product quality, price perception and promotion on repurchase interest among consumers who use Scarlett Skincare in Semarang City. This research was conducted on scarlett skincare users in Semarang City. This analysis uses multiple regression tools, then to test the results of the hypothesis using the t test. The results of data collection through this questionnaire using a Likert scale measurement of 1-5 points to answer several statements. The method of taking this sample will use a purposive sampling technique and the results of this study use a sample of 100 respondents. The results of this study indicate that the results of Product Quality have a positive and significant effect on Repurchase Intention, Price Perception has a positive and significant effect on Repurchase Intention. Still, the results of Promotion do not affect Repurchase Intention.